2018
DOI: 10.1103/physrevb.98.245132
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal investigation of the proposed type-II Weyl semimetal CeAlGe

Abstract: We present details of materials synthesis, crystal structure, and anisotropic magnetic properties of single crystals of CeAlGe, a proposed type-II Weyl semimetal. Single-crystal x-ray diffraction confirms that CeAlGe forms in noncentrosymmetric I41md space group, in line with predictions of non-trivial topology. Magnetization, specific heat and electrical transport measurements were used to confirm antiferromagnetic order below 5 K, with an estimated magnon excitation gap of ∆ = 9.11 K from heat capacity and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 20 publications
14
78
1
Order By: Relevance
“…Using a scanning electron microscope (SEM), we performed an EDS analysis on several powder and single-crystal samples prepared by all the above-described methods. This characterization is crucial, since both the structure type and physical property transition temperatures can vary according to small compositional variations of RAl x Ge 2−x [17,21].…”
Section: Elemental Analysis (Eds)mentioning
confidence: 99%
See 3 more Smart Citations
“…Using a scanning electron microscope (SEM), we performed an EDS analysis on several powder and single-crystal samples prepared by all the above-described methods. This characterization is crucial, since both the structure type and physical property transition temperatures can vary according to small compositional variations of RAl x Ge 2−x [17,21].…”
Section: Elemental Analysis (Eds)mentioning
confidence: 99%
“…For CeAlGe contradictory results have been published for the magnetic properties; early bulk susceptibility data show the magnetic Ce ions to order below ∼6 K, but the system has been reported to order as a ferromagnet (FM) [20] and an antiferromagnet (AFM) [17]. Most recently, a study on flux-grown CeAlGe single crystals was reported [21], with bulk magnetization measurements evidencing ferromagnetic coupling in one direction, and antiferromagnetic coupling in another, apparently resolving contradictions so far. In more detail, the identified easy axis of [100] suggested antiferromagnetic order in the ab plane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14] It turns out that many of these multiferroics and topological magnets are AFM. 5,[10][11][12][14][15][16][17] Spintronics where spin and charge degrees of freedom are mutually coupled and manipulated through crossing conjugate fields (i.e. electric fields for spins and magnetic fields for charges) has been an active research area for the last three decades since the discovery of giant magnetoresistance, and has been well implemented in real devices.…”
Section: Introduction To Afm Domains and Domain Wallsmentioning
confidence: 99%